A COMPREHENSIVE ANALYSIS OF MICROBIAL CONTAMINATION ON MEDICAL PROFESSIONALS ATTIRE AND DEVICES - SHAIKH , M; ZAMEER , S; DEVI , D; AHMED , Z; KHOSO , FM; SHAIKH , AP; AAMIR , K; RAMZAN , A (Biological and Clinical Sciences Research Journal, 2023)
This research aimed to evaluate the level of microbiological contamination on the hands, white coats, and cell phones of healthcare workers. The study was conducted as a cross-sectional study at the Pathology Department of Civil Hospital LUMHS Hyderabad between January 2021 and June 2021. A total of 130 participants were selected using convenience sampling and provided samples. Before sample collection, informed consent was obtained from all participants. Samples were randomly collected from the hands of healthcare professionals, white coats, and various cell phones. Data analysis was performed using SPSS 23.0. In our study, 86 (66.2%) were females and 44 (33.8%) were males. There were 46 (35.4%) cases age 20-30 years, 34 (26.2%) cases aged 31-40 years, 28 (21.5%) cases had age 41-50 years, and 22 (16.9%) cases had age >50 years. 62 (47.7%) samples were taken from lab coats, 43 (33.1%) from the hand of healthcare workers, and 25 (19.2%) from cell phones. The results of the lab coat contamination analysis revealed the following: Methicillin-Resistant Staphylococcus aureus MRSA (6%), Escherichia coli (8%), Pseudomonas (2%), Klebsiella (3%), and Staphylococcus aureus (65%). Healthcare workers who were observed had a majority of MRSA (35.4%), Staphylococcus aureus (33.1%), Staphylococcus epidermidis (26.2%), and Pseudomonas (5%) on their hands. The most common bacteria found on mobile phones were MRSA (40%), followed by Staphylococcus aureus (18%), Staphylococcus epidermidis (34%), and pseudomonas (8%). This study demonstrates that a significant portion of the clothing and personal items used by healthcare professionals were tainted with different microorganisms that can cause nosocomial infections.